Persepsi Masyarakat terhadap Fenomena Pindah Partai oleh Calon Legislatif 2014 di Kabupaten Wonogiri - Esti Sarirani; Yuwanto .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2015)
Reformation era have been promising free and wide space in every life of the nation aspects, especially political aspect. Starting from the freedom to express political opinions to political behavior by politicians. Towards of the 2014’s legislative election in Indonesia, political agitation has occured in both the national and local levels. It also occurs in Wonogiri regency, where there is phenomenon of the moved-political-party by the legislative candidates in the case to fight the position as Wonogiri’s parliament member for 2014 to 2019.Public as the highest authority who noted as the voters in every general election has a very important role to vote the good public representatives. In fact, public now are2confronted with afield behaviors of the legislative candidates, so the trust and award for the legislature are getting lower. The phenomenon of legislative candidate’s movement in exchange nomination in Wonogiri regency had completing the problems.The goals in this thesis writing is to know how are the public perception about the moved-party’s politician by the 2014’s legislative candidates in Wonogiri regency. The type of research is quantitative descriptive.Perseption is the output from objects or informations which captured by human senses. The results of this study indicate that sufficient public attention to the phenomenon of the party moved among the legislative candidates in Wonogiri. Most of the Wonogiri’s public as the renpondents said that they assume this behavior is something that is negative and driven by personal motivation from each candidates. In addition, the belief that a majority of respondents to the public as the party moved legislative candidates in Wonogiri is in the lower level. It shows that there is a negative sentiment from public to the phenomenon of legislative candidate’s movement in Wonogiri regency.Keywords: public perception, legislative candidate’s movement, the legislative’s election.